Syndromic Surveillance of Norovirus Using over the Counter Sales of Medications related to Gastrointestinal Illness - Victoria L Edge; Frank Pollari; Lai King; Pascal Michel; Scott A McEwen; Jeffrey B Wilson; Michael Jerrett; Paul N Sockett; S Wayne Martin (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVE: To assess whether over-the-counter (OTC) sales of gastrointestinal illness (GI)-related medications are associated with temporal trends of reportable community viral, bacterial and parasitic infections.